2003
DOI: 10.7888/juoeh.25.441
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Effect of Lateral Wedge on Hemiplegic Weight Bearing

Abstract: The purpose of this study was to investigate the influence of the lateral wedge on asymmetrical weight bearing and posture in hemiplegic gait. The subjects were 2-female and 4-male moderate stroke patients, average age 54 +/- 6 yr. The time from onset was 127 +/- 69.7 days. A 7 mm-thick wedged insole was applied to the affected side for a week. Before and after that, the vertical ground reaction force, single supporting period and side movement of the trunk were recorded during walking. As a result, we found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Although those with abnormal supination may benefit from a lateral wedge; those with abnormal pronation would require a medial wedge. Some studies have suggested using a lateral sole wedge on the affected or non-affected side to improve balance or other gait parameters, 26,27 but our data suggest that this may adversely affect the feet of many stroke patients. Research on healthy participants has shown that a lateral wedge may increase the velocity of muscle plantarflexor and invertor muscle lengthening.…”
Section: Discussionmentioning
confidence: 57%
“…Although those with abnormal supination may benefit from a lateral wedge; those with abnormal pronation would require a medial wedge. Some studies have suggested using a lateral sole wedge on the affected or non-affected side to improve balance or other gait parameters, 26,27 but our data suggest that this may adversely affect the feet of many stroke patients. Research on healthy participants has shown that a lateral wedge may increase the velocity of muscle plantarflexor and invertor muscle lengthening.…”
Section: Discussionmentioning
confidence: 57%
“…Corrective insoles can change the pressure distribution on the sole to provide an appropriate base of support, maintain correct positioning of the foot to limit or facilitate the movement of the lower limbs as well as enhance shock absorption and stability to alleviate pain or other specific pathologies while standing or walking [17]. Previous research has demonstrated that lateral-wedged and heel-lift insoles had a positive effect by increasing the weight-bearing of the hemiplegic side and bilateral symmetry during standing, but these effects were not felt during ambulation [18,19]. Kusumoto et al confirmed that the insoles combined with a metatarsal pad promoted static and dynamic balance in patients with cerebral palsy [20].…”
Section: Introductionmentioning
confidence: 99%
“…5 The most widely used foot orthosis for patients with stroke is the lateral wedge orthosis which is prescribed to improve balance and gait and correct varus deformity. [6][7][8] Previous studies have demonstrated that wedgeshaped orthoses can influence electromyographic activity of lower limb muscles in the normal population. 9,10 If this is also the case in patients with neurological conditions, then orthotic design could positively or adversely affect muscle activity and consequently, function.…”
Section: Introductionmentioning
confidence: 99%
“…There is however, clinical and objective evidence that orthoses can modify foot and ankle biomechanics 4 and elicit neuromuscular responses 5 . The most widely used foot orthosis for patients with stroke is the lateral wedge orthosis which is prescribed to improve balance and gait and correct varus deformity 6–8 . Previous studies have demonstrated that wedge-shaped orthoses can influence electromyographic activity of lower limb muscles in the normal population 9,10 .…”
Section: Introductionmentioning
confidence: 99%